2009
DOI: 10.1007/s10585-009-9295-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of primary and metastatic colon cancers identifies a reduced proliferative rate in metastatic tumors

Abstract: The objective of this study was to gain insights into the biological basis of the metastatic process by characterizing the gene expression differences between primary and metastatic colon cancers. Recent studies have demonstrated that few new mutational changes are acquired during the metastatic progression of colon tumors [Jones et al., Proc Natl Acad Sci USA 105 (11): 4283-4288, 2008]. However, the extent to which epigenetic and transcriptional changes occur between primary and metastatic colon cancer remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…As opposed to previous studies that have used healthy versus diseased states (29), we rather chose to compare nonmetastatic tumors versus metastatic primary tumors and metastases, to define a gene signature of metastatic potential rather than a general cancer signature. Several groups have studied the gene-expression differences between primary and metastatic colon cancers to explain the molecular basis of the metastatic process and predict clinical outcomes (25,(30)(31)(32). In this study, we decided to employ the reproducible gene-expression signature from (25) that emerged as a consensus from two independent comparisons of Dukes' stage D versus stage A colorectal cancers (Supplementary Table S3; for details see Materials and Methods).…”
Section: Prediction Of Novel Drug Compounds For Metastatic Colorectalmentioning
confidence: 99%
“…As opposed to previous studies that have used healthy versus diseased states (29), we rather chose to compare nonmetastatic tumors versus metastatic primary tumors and metastases, to define a gene signature of metastatic potential rather than a general cancer signature. Several groups have studied the gene-expression differences between primary and metastatic colon cancers to explain the molecular basis of the metastatic process and predict clinical outcomes (25,(30)(31)(32). In this study, we decided to employ the reproducible gene-expression signature from (25) that emerged as a consensus from two independent comparisons of Dukes' stage D versus stage A colorectal cancers (Supplementary Table S3; for details see Materials and Methods).…”
Section: Prediction Of Novel Drug Compounds For Metastatic Colorectalmentioning
confidence: 99%
“…It shows that metastasis is a highly inefficient system due to many factors which are important during the first twenty four hour period when the cell is adhering to a new micro environment. In our study of colorectal metastasis to the liver [1], we have identified a reduced proliferative role in the metastasic tumor compared to the primary. Here, cancer cell autophagy plays a role in the immediate survival of the cell in a totally foreign environment after its dislocation from the primary site.…”
Section: Cancer Cell Metastasismentioning
confidence: 82%
“…Accompanying this was the lower proliferation in SW620 and the NDRG1-siRNA-treated SW480. Interestingly, it was reported recently that a global survey of colon cancers revealed that metastatic colon cancers have reduced proliferation compared to primary tumors [22]. The study showed that cell cycle gene expression along with Ki67 staining was decreased in metastatic tumors compared to primary tumors.…”
Section: Discussionmentioning
confidence: 92%